Slope Stability Analysis of Granitic Residual Soil Using SLOPE/W, Resistivity and Seismic - Omar, RC; Baharuddin, INZ; Taha, Hairin; Roslan, R.; NK, Hazwani; MF, Muzad (International Journal of Engineering and Technology, 2018)
There are many factors that influence slope failure such as natural disasters and human activities. Amongst the major causes are the rise of groundwater and infiltration of prolonged and antecedent rainfalls. Together with its geographical condition; high lands and mountains, Malaysia is prone to have landslides especially at the Main Range area where most of the soil is residual soil. This study investigated a slope which had a history of landslide due to circular failure landslide using Slope/W, resistivity and seismic surveys to determine the physical and mechanical properties of the on-site materials. Based on the resistivity survey, the existence of groundwater level has been detected at a depth of 10.0 m from the ground level. Seismic analysis showed that the subsurface area was made up of Weathered Granite Grade VI (sandy soil) which is loose to medium dense. SLOPE/W analysis showed that the factor of safety (FOS) was 0.186 which was unstable for slope stability condition. The assessment showed that the slope condition is still not stable despite slope stabilization measurement using cement grouting. It is proposed that erosion control measures on the slope surface should be implemented to prevent recurrent of slope failure and to ensure slope stability.